The Non-consensus Entrepreneur - Pontikes, Elizabeth G.; Barnett, William P. (Administrative Science Quarterly, 2017)
Salient successes and failures, such as spectacular venture capital investments or agonizing bankruptcies, affect collective beliefs about the viability of particular markets. Using data on software start-ups from 1990 to 2002, we show that collective sense-making in the wake of such vital events can result in consensus behavior among entrepreneurs. Market search is a critical part of the entrepreneurial process, as entrepreneurs frequently enter new markets to find high-growth areas. When spectacular financings result in a collective overstatement of the attractiveness of a market, a consensus emerges that the market is resource-rich, and the path is cleared for many entries, including those that do not have a clear fit. When notorious failures render a market unpopular, only the most viable entrants will overcome exaggerated skepticism and enter, taking the non-consensus route. Venture capitalists likewise exhibit herding behavior, following other VCs into hot markets. We theorize that vital events effectively change the selection threshold for market entries, which changes the average viability of new entrants. We find that consensus entrants are less viable, while non-consensus entrants are more likely to prosper. Non-consensus entrepreneurs who buck the trends are most likely to stay in the market, receive funding, and ultimately go public.